Laboratory Service Process Checklist: Preventive Measures to Increase Blood Glucose Test Accuracy - Setyawan, Yudi; Wardhani, Viera (Jurnal Kedokteran Brawijaya, 2021)
The accuracy of the blood glucose test results is an essential measurement for hospital quality since it affects the plan, decision, and outcome of the treatment. This study aimed to develop a checklists model to improve the laboratory results accuracy. The checklist development is based on the laboratory services processes covering pre-analytic, analytic, and post-analytic stages, which are implemented in all blood glucose test requests during the study period (65 examinations), the first week of October 2020. The implementation resulted in no incidence of test inaccuracy when conformed with patient clinical information. The staff expressed that completing the checklist is quick and easy to complete (3-5 minutes) and beneficial. The problem occurs when staff works alone, causing delays in completing the checklist. Therefore, regular monitoring and evaluation are suggested to ensure compliance and divide the checklist into two stages. The pre-analytic stage is first carried out for all patients, followed by the analytical and post-analytic stages because the last two activities were located on different floors. In short, checklists are effective as preventive measures to increase the conformity of laboratory examination results with patient clinical information.